A framework for determining improved placement of current energy converters subject to environmental constraints - Nelson, Kurt; James, Scott C.; Roberts, Jesse D.; Jones, Craig (International journal of sustainable energy, 2018)
A modelling framework identifies deployment locations for current-energy-capture devices that maximise power output while minimising potential environmental impacts. The framework, based on the Environmental Fluid Dynamics Code, can incorporate site-specific environmental constraints. Over a 29-day period, energy outputs from three array layouts were estimated for: (1) the preliminary configuration (baseline), (2) an updated configuration that accounted for environmental constraints, (3) and an improved configuration subject to no environmental constraints. Of these layouts, array placement that did not consider environmental constraints extracted the most energy from flow (4.38 MW-hr/day), 19% higher than output from the baseline configuration (3.69 MW-hr/day). Array placement that considered environmental constraints removed 4.27 MW-hr/day of energy (16% more than baseline). This analysis framework accounts for bathymetry and flow-pattern variations that typical experimental studies cannot, demonstrating that it is a valuable tool for identifying improved array layouts for field deployments.